X-Culture: An International Project in the Light of Experience Gained over the Years (2010-2016) - Poór, József; Varga, Erika; Renata, Renata; Taras, Vas (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The X-Culture project is an innovative modern form of experiential learning predominantly in International Management and International Business. Although experiential learning has some advantages, namely, developing cross-cultural competencies, cultural intelligence, intercultural communication and management skills, differences in personality or conditions also arise as a downside. X-Culture has been evolving throughout the years since 2010 when the original objective was to supplement the theoretical material and in-class teaching. Nowadays more than 4000 master, bachelor and MBA students, mostly of management and economics from more than 37 countries, take part in the project every semester. X-Culture is aimed at students of International Business college courses and training programs with the task of writing a business report or consulting propositions by offering business solutions for a hypothetical client. This paper outlines the theoretical background of the X-culture project. It describes the evolution and practical and theoretical experience of this project since 2010.